هندسة دستور جزائري جديد بين المطالب البسيطة للحراك الشعبي والقواعد العلمية التقنية - رمضاني, فاطمة الزهراء (جامعة الوادي University of Eloued, 2019)
ملخص: إن عملية إعداد الدساتير محفوفة بالمخاطر في ظل الظروف العادية، فكيف إذن يمكن تيسير عمليّة وضع دستور قائم على أسس علمية بالأخذ برأي الشعب في ظل المتغيرات التي يعرفها المجتمع الجزائري إبتداءا من 22فبراير 2019.؟ من خلال هذه الورقة البحثية سنناقش دور ومشاركة الشعب في وضع الدستور إنطلاقا من مطالب الحراك الشعبي بتطبيق نص المادة السابعة من الدستور، إذ نحاول تسليط الضوء على الجانب التقني لصياغة الدساتير و محاولة الاستقاء من التجارب المقارنة و تبني الأفكار المتماشية مع طبيعة ومتطلبات الشعب الجزائري، وطرح النتائج، والاجتهاد في اقتراح التوصيات بخصوص اعتماد دستور المرحلة المقبلة المتعلقة ببناء دولة القانون. الكلمات المفتاحية: دستور،قواعد تقنية،حراك،صياغة قانونية،مادة 07. Abstract : The process of drafting constitutions is precarious under normal circumstances, so how can this process be based on scientific grounds be facilitated by taking the opinion of the people in the light of the changes that Algerian society knows? Through this paper we will discuss the role and participation of the people in drafting the constitution, based on the demands of the popular movement to implement the Article 7 of the Constitution, as we try to highlight the technical aspect of drafting constitutions and try to draw from comparative experiences, and Put forward the results, and diligence in proposing recommendations regarding the adoption of the Constitution of the next phase relating to the building a state of law. key words : Constitution, Technical Rules, Mobility, Legal Drafting, Article 07.
Engineering A New Algerian Constitution Between The Simple Demands Of The Popular Movement And The Scientific Technical Rules
Keywords: دستور، قواعد تقنية، حراك، صياغة قانونية، مادة 07; Constitution, Technical Rules, Mobility, Legal Drafting, Article 07.